Histone Demethylase JMJD2C Is Stage-Specifically Expressed in Preimplantation Mouse Embryos and Is Required for Embryonic Development - Wang, Jianle; Zhang, Miao; Zhang, Yu; Kou, Zhaohui; Han, Zhiming; Chen, Da-Yuan; Sun, Qing-Yuan; Gao, Shaorong (Biology of reproduction, 2010)
Epigenetic modifications play a pivotal role in embryonic development by dynamically regulating DNA methylation and chromatin modifications. Although recent studies have shown that core histone methylation is reversible, very few studies have investigated the functions of the newly discovered histone demethylases during embryonic development. In the present study, we investigated the expression characteristics and function of JMJD2C, a histone demethylase that belongs to the JmjC-domain-containing histone demethylases, during preimplantation embryonic development of the mouse. We found that JMJD2C is stage-specifically expressed during preimplantation development, with the highest activity being observed from the two-cell to the eight-cell stage. Depletion of JMJD2C in metaphase II oocytes followed by parthenogenetic activation causes a developmental arrest before the blastocyst stage. Moreover, consistent with a previous finding in embryonic stem (ES) cells, depletion of JMJD2C causes a significant down-regulation of the pluripotency gene Nanog in embryos. However, contrary to a previous report in ES cells, we observed that other pluripotency genes, Pou5f1 and Sox2, are also significantly down-regulated in JMJD2C-depleted embryos. Furthermore, the depletion of JMJD2C in early embryos also caused significant down-regulation of the Myc and Klf4 genes, which are associated with cell proliferation. Our data suggest that the deregulation of these critical genes synergistically causes the developmental defects observed in JMJD2C-depleted embryos.